Regulation of γδ T Cell Effector Diversification in the Thymus - Parker, Morgan E.; Ciofani, Maria (Frontiers in Immunology, 2020)
gd T cells are the first T cell lineage to develop in the thymus and take up residence in a wide variety of tissues where they can provide fast, innate-like sources of effector cytokines for barrier defense. In contrast to conventional ab T cells that egress the thymus as naïve cells, gd T cells can be programmed for effector function during development in the thymus. Understanding the molecular mechanisms that determine gd T cell effector fate is of great interest due to the wide-spread tissue distribution of gd T cells and their roles in pathogen clearance, immunosurveillance, cancer, and autoimmune diseases. In this review, we will integrate the current understanding of the role of the T cell receptor, environmental signals, and transcription factor networks in controlling mouse innate-like gd T cell effector commitment.